Educating black youth through Hip-Hop studies (Revista Educação, Artes e Inclusão, 2020)
This essay explores educational performance between blacks and whites in the United States and the various reasons research has given for the education gap in America. It explores both the class and race based arguments for the gap, but interjects a cultural explanation and underlying “orienting concepts” as more salient reasons for the education gap. It debunk the “cultural deprivation model” for low by blacks, and argues for actually utilizing the prolific cultural contributions of black culture in teaching methodology, particularly in higher education. It explores Critical Race Theory, as well as Social Justice Hip-Hop Pedagogy theory to examine alternative explanations for the problem and methods to ameliorate it. Through the use of one case study, examples of how Hip-Hop Studies is shown to achieve success in making education relevant to university students of color, and black students in particular, which has implications for elementary and secondary education as well.
Keywords: Education Gap; Racism in Education; Critical Race Theory; Hip-Hop Studies